An in-depth analysis of the sexuality needs of Barcelona's youth: a holistic view using mixed method. Issue 1 (31st December 2022) - Forcadell-Díez, Lluís; Benlliure, Jordi Baroja; Martínez, Cristina; Pérez, Gloria
Abstract: A positive experience of sexuality during youth is key to good sexual health later in life. Addressing young people's sexual health needs and sexual and reproductive rights is thus essential. This study aimed to identify unmet sexual health needs among youth in the city of Barcelona (Spain) through mixed methods research. We analysed the narratives of young people ( n  = 50) aged 14–24 years with different genders, origins, sexualities and socioeconomic backgrounds, collected from January to April 2019. A descriptive statistical analysis was also conducted on the records of visits to sexual health services and reasons for consultation. We found that 21% ( n  = 32, 161) of young people aged 14–24 years had used sexual healthcare services in Barcelona between 2015 and 2017, while the reasons for consultation differed across sex, gender and socioeconomic background. Young people declared that they needed more information to enjoy their sexuality, to know where to go in case of an unexpected situation and to learn how to combat gender-based violence. They stated that the sexuality education they had received was sparse and focused on risks. We found that formal sex education is scarce, with informal sex education thus acquiring a major role. Current services can be improved by expanding coverage, training professionals and reducing acceptability and accessibility barriers. Sexism is ubiquitous in young people's sexual, dating and personal relationships. We recommend planning sexual health care services and formal sexual education, in which a strong gender strategy is embedded, as part of the same strategy.